2019
DOI: 10.1007/s11747-019-00680-8
|View full text |Cite
|
Sign up to set email alerts
|

Technology readiness: a meta-analysis of conceptualizations of the construct and its impact on technology usage

Abstract: The technology readiness (TR) index aims to better understand people's propensity to embrace and use cutting-edge technologies. The initial TR construct considers four dimensions-innovativeness, optimism, insecurity, and discomfort-that collectively explain technology usage. The present meta-analysis advances understanding of TR by reexamining its dimensionality, and investigating mediating mechanisms and moderating influences in the TR-technology usage relationship. Using data from 193 independent samples ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
245
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(272 citation statements)
references
References 95 publications
(153 reference statements)
20
245
4
3
Order By: Relevance
“…Finally, this study focused only on three demographic variables (i.e., gender, major of study, and computer ownership), which are among the important variables that may have a role in students' readiness for a technology-based learning environment, such as CSCL. Future research can study the possible roles of other variables, such as age, previous experience, education, nationality, and cultural values [97,98], in students' readiness for CSCL.…”
Section: Limitations and Suggestions For Further Researchmentioning
confidence: 99%
“…Finally, this study focused only on three demographic variables (i.e., gender, major of study, and computer ownership), which are among the important variables that may have a role in students' readiness for a technology-based learning environment, such as CSCL. Future research can study the possible roles of other variables, such as age, previous experience, education, nationality, and cultural values [97,98], in students' readiness for CSCL.…”
Section: Limitations and Suggestions For Further Researchmentioning
confidence: 99%
“…In the literature, TR is either considered important that warrant further usage or one that is ignored by researchers due to its insignificance. Blut and Wang (2019) for instance, are the proponents of TR as an important concept which is useful in linking people's behaviour in technology adoption. As they argue, the results from the investigation between TR and adoption are useful to marketers in identifying segments of customers that are ready or not ready to adopt new technology.…”
Section: Importance and Neglect Of Trmentioning
confidence: 99%
“…This view emerged as TR is observed to be not popular and is still not as widely applied by researchers in comparison to other adoption theories like the technology acceptance model (TAM) or diffusion of innovation (DOI) theory (Humbani, 2018). The neglect of TR may be due to criticism of the inconsistency of TR's influence on technology use (Blut & Wang, 2019;Lundberg, 2017). According to Blut and Wang (2019), past studies' findings in regards to TR and technology usage relationships have often been found to be inconsistent with some studies that showed significant support in the relationships tested (e.g.…”
Section: Importance and Neglect Of Trmentioning
confidence: 99%
See 2 more Smart Citations